Preparation method and application of Al2O3 solid-phase coated lithium-rich manganese-based single-crystal positive electrode material

The lithium-rich manganese single crystal positive electrode material was prepared by co-precipitation method and Al2O3 solid phase coated, which solved the problem of unstable structure during the circulation process, improved the electrochemical performance and cycle life, and achieved an efficient and economical preparation process.

CN119742328AInactive Publication Date: 2025-04-01GUANGDONG JIANA ENERGY TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411817835.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials are prone to cracks and structural instability during the circulation process, resulting in a decrease in electrochemical performance. In addition, the industrial preparation methods have problems with component uniformity and cation mixed discharge, which makes the preparation cost high.

Method used

The submicron precursor was prepared by co-precipitation method, and the submicron small-particle size lithium-manganese single crystal positive electrode material was obtained by oxidation and sintering molding. It was then coated with Al2O3 solid phase to suppress side reactions.

Benefits of technology

It significantly improves the electrochemical performance of lithium-rich manganese-based single-crystal positive electrode material, extends the cycle life, reduces side reactions, and has a simple and efficient process, which is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742328A_ABST
    Figure CN119742328A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an Al2O3 solid-phase coated lithium-rich manganese-based single-crystal positive electrode material. The preparation method comprises the following steps: S1, preparing a transition metal salt solution, a NaOH aqueous solution and a NH3.H2O mixed solution; s2, the transition metal salt solution and the mixed solution of NaOH and NH3.H2O are pumped into a reactor at the same time, the pH value of the reaction is controlled to be kept at 11-12, and a [NixMny] (OH) 2 precursor is obtained; s3, pre-sintering the [NixMny] (OH) 2 precursor in a pure oxygen atmosphere; and S4, mixing the sintered [NixMny] (OH) 2 precursor with a lithium source, and carrying out secondary roasting to obtain the submicron small-particle-size lithium-rich manganese-based single crystal positive electrode material. S5, uniformly mixing the lithium-rich manganese-based single-crystal positive electrode material with a certain proportion of Al2O3 solid phase, and carrying out heat preservation and annealing to obtain an Al2O3 coated lithium-rich manganese-based single-crystal positive electrode material Li < 1.2 > Ni < x > Mn < y > O < 2 > (at) Al2O3; the Li < 1.2 > Ni < x > Mn < y > O < 2 > (at) Al < 2 > O < 3 > prepared by the method is used for preparing a positive pole piece, and the positive pole piece is applied to a lithium ion battery; the positive electrode material prepared by the method disclosed by the invention has good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a preparation method and application of an Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material. Background Art

[0002] Lithium-rich manganese-based materials exhibit superior electrochemical properties due to their unique crystal structure and composition. Their unique transition metal redox and anion redox mechanisms give lithium-rich manganese-based materials extremely high theoretical specific capacity and a wide voltage platform, making their energy density far higher than the lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate and ternary materials currently widely used in commercial applications. In addition, lithium-rich manganese-based materials do not use expensive metal cobalt, greatly reducing material costs. This economic advantage makes it a leader in the next generation of lithium-ion battery positive electrode materials, with broad application prospects in the market.

[0003] The electrochemical performance of lithium-rich manganese-based cathode materials is closely related to the particle size. At present, the mainstream on the market is still polycrystalline lithium-rich manganese-based cathode materials. Since the particles of polycrystalline cathode materials are anisotropic, microcracks on the surface during the cycle will also cause structural instability and more side reactions in the subsequent process. Therefore, a single crystal structure with less internal stress can effectively eliminate microcracks during lithiation and abrasion, thereby improving the cycle life and specific capacity. Coating small-particle single crystals with metal oxides is a feasible means of single crystal modification.

[0004] At present, the mainstream industrial preparation methods for layered oxide single crystal cathode materials, including lithium-rich manganese-based materials, are hydrothermal or sol-gel methods, but they both face the problems of uniformity of ions of each component and mixed arrangement of cations. In addition, the sol-gel method requires expensive organic reagents, high preparation cost and long cycle, so it cannot be applied on a large scale. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a preparation method and application of Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material. On the basis of co-precipitation reaction, a submicron precursor is generated, and through subsequent oxidation and sintering molding treatment, submicron-level small-particle lithium-rich manganese single crystal positive electrode particles are obtained, which solves the uniformity of each component ion and the mixing of cations; and then by solid-phase coating Al2O3, the side reactions of small-particle single crystal positive electrode materials in the cycle process are effectively suppressed.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] A method for preparing an Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material comprises the following steps:

[0008] S1. Solution preparation: prepare a transition metal salt solution at a molar ratio of Ni:Mn=1:(2.2-3), and simultaneously prepare a NaOH aqueous solution and an NH3·H2O aqueous solution;

[0009] S2. Preparation of small particle size precursor: The transition metal salt solution, NaOH aqueous solution and NH3·H2O aqueous solution are slowly pumped into a reactor containing NaOH and deionized water at the same time, and the pH value of the reaction is controlled to be maintained at 11-12. After the reaction is completed, [Ni x Mn y ](OH)2 precursor, wherein 0.25≤x≤0.3125,0.6875≤y≤0.75, the [Ni x Mn y ]The particle size of the (OH)2 precursor is 1-4 microns;

[0010] S3, small particle size precursor surface pre-oxidation: the [Ni x Mn y ](OH)2 precursor is pre-sintered in a pure oxygen atmosphere;

[0011] S4, the pre-sintered [Ni x Mn y ](OH)2 precursor is mixed with lithium source and calcined twice in oxygen atmosphere to obtain submicron-sized lithium-rich manganese-based single crystal cathode material Li 1.2 Ni x Mn y O2, where 0.20≤x≤0.25, 0.55≤y≤0.60;

[0012] S5, mixing the lithium-rich manganese-based single crystal positive electrode material and Al2O3 solid phase uniformly, and annealing at 400-500°C to obtain Al2O3-coated lithium-rich manganese-based single crystal positive electrode material Li 1.2 Ni x Mn y O2@Al2O3.

[0013] Furthermore, in step S1, the transition metal salt solution Ni 2+ and Mn 2+ The total concentration is 2-4 mol L -1 ; The concentration of the NaOH aqueous solution is 4-6 mol L -1 The concentration of the NH3·H2O aqueous solution is 2-6 mol L -1 .

[0014] Furthermore, in step S1, the transition metal salt is selected from one of sulfate, chloride and nitrate, and the sulfate is NiSO4·6H2O and / or MnSO4·H2O.

[0015] Furthermore, during the preparation of the small-particle precursor in step S2, the reaction temperature is controlled at 50-55° C., and stirring is performed continuously in the protective atmosphere of inert protective gas at a stirring rate of 700-900 rpm.

[0016] Furthermore, the pre-sintering temperature in step S3 is 400-500° C., and the time is 300-360 min.

[0017] Furthermore, the lithium source in step S4 is selected from at least one of LiOH·H2O, LiNO3, and Li2CO3; the pre-sintered [Ni x Mn y ]The molar ratio of the (OH)2 precursor to the lithium source is 1:(1.50-1.60).

[0018] Furthermore, the secondary calcination in step S4 is specifically as follows: heating to 500-600°C at a heating rate of 2°C / min-5°C / min in an oxygen atmosphere, and keeping the temperature for 6-8 hours for sintering; then heating to 800-950°C, and keeping the temperature for 10-15 hours for solid phase lithium insertion reaction.

[0019] Furthermore, the coating amount of Al2O3 is 1-5wt% of the lithium-rich manganese-based single crystal positive electrode material.

[0020] A positive electrode plate is prepared by coating a slurry made of the Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material, a conductive agent, a binder and a solvent.

[0021] A lithium-ion battery, comprising the positive electrode sheet and the negative electrode sheet;

[0022] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.

[0023] The beneficial effects brought about by the technical solution provided by the present invention include at least:

[0024] The present invention provides a technology for preparing lithium-rich manganese-based single crystal materials by coprecipitation, which overcomes the problem that polycrystalline lithium-rich manganese-based positive electrode materials are prone to cracks and performance degradation during circulation. Through the coprecipitation method, different metal ions or compounds are uniformly mixed in the same solution to promote nucleation and crystal growth, thereby enhancing the crystallinity of the crystal. By controlling the temperature and pH value, the precipitation rate can be adjusted to avoid uneven precipitation and crystal defects, which is conducive to the formation of single crystals. In addition, the solvent used can optimize the chemical environment, reduce impurity incorporation, and prevent the formation of polycrystalline or defective crystals. The slower precipitation rate also helps to adjust the crystal structure, thereby reducing defects. Through the configuration of the precursor solution, the optimization of the complexing agent and the precipitant, and the subsequent oxidation and sintering processes, a lithium-rich manganese-based single crystal material with good crystallinity and uniform and controllable components is successfully prepared. This material significantly improves the electrochemical performance of lithium-rich manganese-based single crystal positive electrode materials, and effectively suppresses the side reactions of small-size single crystals during the circulation process by coating Al2O3. The process flow is simple and efficient, and is suitable for large-scale application.

[0025] According to the material and calcination conditions, a slightly excessive amount of lithium source is added in the present invention, and the molar percentage of the excess lithium source is 5-10%, which balances the volatilization of lithium during the high-temperature lithium insertion process and slows down the mixing of Li / Ni in the lattice. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 [Ni prepared in Example 1 x Mn y ]SEM image of (OH)2 precursor.

[0027] Figure 2 This is a SEM image of the lithium-rich manganese-based single crystal positive electrode material prepared in Example 1. Figure 3 This is a diagram showing the cycling effect of the Al2O3-coated lithium-rich manganese-based single crystal positive electrode material of Example 1. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0029] Example 1

[0030] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ , Mn 2+ The molar ratio of Ni is 1:3. 2+ , Mn 2+ The sum of the concentrations is 2 mol / L, and 4 mol / L ammonia water and 4 mol / L NaOH solution are prepared.

[0031] S2. Preparation of precursor: 2L of transition metal salt solution was added into a reactor with a nitrogen atmosphere and a rotation speed of 800rpm at a rate of 0.2L / h, 4mol / L of ammonia water was added into the reactor as a complexing agent, and 4mol / L of NaOH solution was pumped into the reactor at the same time. The flow rate of the alkaline solution was adjusted to maintain the pH value between 11.3 and 11.4, and a coprecipitation reaction was performed to prepare the precursor [Ni 0.25 Mn 0.75 ](OH)2. As the size of the hydroxide precursor increases, samples are taken every 2 hours. 50 When the particle size reaches 1-2 microns, the heating is turned off after the reaction is completed, and the precursor is washed with water and filtered after aging for 12 hours;

[0032] S3, precursor pre-oxidation: the [Ni 0.25 Mn 0.75 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 500°C at a heating rate of 100°C and kept at that temperature for 300 minutes for pre-oxidation;

[0033] S4, high temperature solid phase lithium insertion: the precursor obtained after sintering was mixed evenly with LiOH·H2O with a chemical molar ratio of 1:1.55 with lithium atoms. Then, the collected black precursor was placed in a muffle furnace and heated at 3℃min in an oxygen atmosphere. -1 The temperature was raised to 550°C and kept for 400 min, then raised to 870°C and kept for 720 min for solid phase lithium insertion reaction. After calcination, single crystal positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2;

[0034] S5, mixing the lithium-rich manganese-based single crystal positive electrode material and Al2O3 solid phase uniformly, and annealing at 400°C to obtain Al2O3-coated lithium-rich manganese-based single crystal positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2@Al2O3, the coating amount of Al2O3 is 1wt% of the lithium-rich manganese-based single crystal positive electrode material.

[0035] A positive electrode plate is prepared by coating a slurry made of Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material, a conductive agent, a binder and a solvent.

[0036] A lithium-ion battery, comprising the positive electrode sheet and the negative electrode sheet;

[0037] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.

[0038] Example 2

[0039] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ , Mn 2+ The molar ratio of Ni is 1:3. 2+ , Mn 2+ The sum of the concentrations is 2 mol / L, and 4 mol / L ammonia water and 6 mol / L NaOH solution are prepared;

[0040] S2. Preparation of precursor: 2L of transition metal salt solution was added into a reactor with a nitrogen atmosphere and a rotation speed of 800rpm at a rate of 0.2L / h, 4mol / L of ammonia water was added into the reactor as a complexing agent, and 6mol / L of NaOH solution was pumped into the reactor at the same time. The flow rate of the alkaline solution was adjusted to maintain the pH value between 11.3-11.4, and a coprecipitation reaction was performed to prepare the precursor [Ni 0.25 Mn 0.75 ](OH)2. As the size of the hydroxide precursor increases, samples are taken every 2 hours. 50 When the particle size reaches 1-2 microns, the heating is turned off after the reaction is completed, and the precursor is washed with water and filtered after aging for 12 hours;

[0041] S3, precursor pre-oxidation: the [Ni 0.25 Mn 0.75 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 500°C at a heating rate of 100°C and kept at that temperature for 300 minutes for pre-oxidation;

[0042] S4, high temperature solid phase lithium insertion: the precursor obtained after sintering was mixed with lithium atoms at a chemical molar ratio of 1:1.55. Then, the collected black precursor was placed in a muffle furnace and heated at 3℃min in an oxygen atmosphere. -1 The temperature was raised to 550°C and kept for 400 min, then raised to 870°C and kept for 720 min for solid phase lithium insertion reaction. After calcination, single crystal positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2;

[0043] S5, mixing the lithium-rich manganese-based single crystal positive electrode material and Al2O3 solid phase uniformly, and annealing at 400°C to obtain Al2O3-coated lithium-rich manganese-based single crystal positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2@Al2O3, the coating amount of Al2O3 is 3wt% of the lithium-rich manganese-based single crystal positive electrode material.

[0044] A positive electrode plate is prepared by coating a slurry made of Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material, a conductive agent, a binder and a solvent.

[0045] A lithium-ion battery, comprising the positive electrode sheet and the negative electrode sheet;

[0046] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.

[0047] Example 3

[0048] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ , Mn 2+ The molar ratio of Ni is 1:3. 2+ , Mn 2+ The sum of the concentrations is 2 mol / L, and 4 mol / L of ammonia water and 4 mol / L of NaOH solution are prepared.

[0049] S2. Preparation of precursor: 2L of transition metal salt solution was added into a reactor with a nitrogen atmosphere and a rotation speed of 800rpm at a rate of 0.2L / h, 4mol / L of ammonia water was added into the reactor as a complexing agent, and 4mol / L of NaOH solution was pumped into the reactor at the same time. The flow rate of the alkaline solution was adjusted to maintain the pH value between 11.3 and 11.4, and a coprecipitation reaction was performed to prepare the precursor [Ni 0.25 Mn 0.75 ](OH)2. As the size of the hydroxide precursor increases, samples are taken every 2 hours. 50 When the particle size reaches 1-2 microns, the heating is turned off after the reaction is completed, and the precursor is washed with water and filtered after aging for 12 hours;

[0050] S3, precursor pre-oxidation: the [Ni 0.25 Mn 0.75 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 500°C at a heating rate of 100°C and kept at that temperature for 300 minutes for pre-oxidation;

[0051] S4, high temperature solid phase lithium insertion: the precursor obtained after sintering was mixed evenly with LiOH·H2O with a stoichiometric ratio of lithium atoms exceeding 1:1.55. Subsequently, the collected black precursor was placed in a muffle furnace and heated at 3℃min in an oxygen atmosphere. -1 The temperature was raised to 550°C and kept for 400 min; then the temperature was raised to 870°C and kept for 720 min for solid phase lithium insertion reaction. After calcination, the single crystal positive electrode material Li 1.2 Ni 0.2 Mn0.6 O2;

[0052] S5, mixing the lithium-rich manganese-based single crystal positive electrode material and Al2O3 solid phase uniformly, and annealing at 400°C to obtain Al2O3-coated lithium-rich manganese-based single crystal positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2@Al2O3, the coating amount of Al2O3 is 5wt% of the lithium-rich manganese-based single crystal positive electrode material.

[0053] A positive electrode plate is prepared by coating a slurry made of Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material, a conductive agent, a binder and a solvent.

[0054] A lithium-ion battery, comprising the positive electrode sheet and the negative electrode sheet;

[0055] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.

[0056] Example 4

[0057] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ , Mn 2+ The molar ratio of Ni is 1:2.2. 2+ , Mn 2+ The sum of the concentrations is 3 mol / L, and 2 mol / L ammonia water and 6 mol / L NaOH solution are prepared.

[0058] S2. Preparation of precursor: 2L of transition metal salt solution was added into a reactor with a nitrogen atmosphere and a rotation speed of 800rpm at a rate of 0.2L / h. 2mol / L of ammonia water was added into the reactor as a complexing agent. At the same time, 6mol / L of NaOH solution was pumped into the reactor. The flow rate of the alkaline solution was adjusted to maintain the pH value between 11-11.5. A coprecipitation reaction was performed to prepare the precursor [Ni 0.3125 Mn 0.6875 ](OH)2. As the size of the hydroxide precursor increases, samples are taken every 1.5 hours. 50 When the particle size reaches 2-3 microns, the heating is turned off after the reaction is completed, and the precursor is washed with water and filtered after aging for 12 hours;

[0059] S3, precursor pre-oxidation: the [Ni 0.3125 Mn 0.6875 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 400°C at a heating rate of 10000 °C and kept at that temperature for 320 min for pre-oxidation;

[0060] S4, high temperature solid phase lithium insertion: the precursor obtained after sintering was mixed evenly with LiNO3 in a stoichiometric ratio of 1:1.50 with lithium atoms. Subsequently, the collected black precursor was placed in a muffle furnace and heated at 2℃min in an oxygen atmosphere. -1 The temperature was raised to 500°C and kept for 360 minutes. The temperature was then raised to 800°C and kept for 600 minutes for solid phase lithium insertion reaction. After calcination, the single crystal positive electrode material Li 1.2 Ni 0.25 Mn 0.55 O2;

[0061] S5, mixing the lithium-rich manganese-based single crystal positive electrode material and Al2O3 solid phase uniformly, and annealing at 400°C to obtain Al2O3-coated lithium-rich manganese-based single crystal positive electrode material Li 1.2 Ni 0.25 Mn 0.55 O2@Al2O3, the coating amount of Al2O3 is 2wt% of the lithium-rich manganese-based single crystal positive electrode material.

[0062] A positive electrode plate is prepared by coating a slurry made of Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material, a conductive agent, a binder and a solvent.

[0063] A lithium-ion battery, comprising the positive electrode sheet and the negative electrode sheet;

[0064] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.

[0065] Example 5

[0066] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ , Mn 2+ The molar ratio of Ni is 1:2.4. 2+ , Mn 2+ The sum of the concentrations is 4 mol / L, and 5 mol / L ammonia water and 5 mol / L NaOH solution are prepared.

[0067] S2. Preparation of precursor: 2L of transition metal salt solution was added into a reactor with a nitrogen atmosphere and a rotation speed of 800rpm at a rate of 0.2L / h, 5mol / L of ammonia water was added into the reactor as a complexing agent, and 5mol / L of NaOH solution was pumped into the reactor at the same time. The flow rate of the alkaline solution was adjusted to maintain the pH value between 11.5 and 11.6, and a coprecipitation reaction was performed to prepare the precursor [Ni 0.295 Mn 0.705](OH)2. As the size of the hydroxide precursor increases, samples are taken every 2 hours. 50 When the particle size reaches 1-2 microns, the heating is turned off after the reaction is completed, and the precursor is washed with water and filtered after aging for 12 hours;

[0068] S3, precursor pre-oxidation: the [Ni 0.295 Mn 0.705 ](OH)2 precursor was heated in pure oxygen atmosphere at 4℃min -1 The temperature was raised to 450°C at a heating rate of 10000 °C and kept at that temperature for 330 min for pre-oxidation;

[0069] S4, high temperature solid phase lithium insertion: the precursor obtained after sintering was mixed evenly with Li2CO3 in a stoichiometric ratio of 1:1.53 with lithium atoms. Subsequently, the collected black precursor was placed in a muffle furnace and heated at 4 °C min in an oxygen atmosphere. -1 The temperature was raised to 580°C and kept for 420 minutes. The temperature was then raised to 900°C and kept for 780 minutes for solid phase lithium insertion reaction. After calcination, the single crystal positive electrode material Li 1.2 Ni 0.235 Mn 0.565 ;

[0070] S5, mixing the lithium-rich manganese-based single crystal positive electrode material and Al2O3 solid phase uniformly, and annealing at 400°C to obtain Al2O3-coated lithium-rich manganese-based single crystal positive electrode material Li 1.2 Ni 0.235 Mn 0.565 O2@Al2O3, the coating amount of Al2O3 is 2.5wt% of the lithium-rich manganese-based single crystal positive electrode material.

[0071] A positive electrode plate is prepared by coating a slurry made of Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material, a conductive agent, a binder and a solvent.

[0072] A lithium-ion battery, comprising the positive electrode sheet and the negative electrode sheet;

[0073] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.

[0074] Example 6

[0075] S1. Solution preparation: Prepare transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ , Mn 2+ The molar ratio of Ni is 1:2.8. 2+ , Mn 2+The sum of the concentrations is 3.8 mol / L, and 6 mol / L of ammonia water and 6 mol / L of NaOH solution are prepared.

[0076] S2. Preparation of precursor: 2L of transition metal salt solution was added into a reactor with a nitrogen atmosphere and a rotation speed of 800rpm at a rate of 0.2L / h, 6mol / L of ammonia water was added into the reactor as a complexing agent, and 6mol / L of NaOH solution was pumped into the reactor at the same time. The flow rate of the alkaline solution was adjusted to maintain the pH value between 11.8 and 12, and a coprecipitation reaction was performed to prepare the precursor [Ni 0.263 Mn 0.737 ](OH)2. As the size of the hydroxide precursor increases, samples are taken every 2 hours. 50 When the particle size reaches 3-4 microns, the heating is turned off after the reaction is completed, and the precursor is washed with water and filtered after aging for 12 hours;

[0077] S3, precursor pre-oxidation: the [Ni 0.263 Mn 0.737 ](OH)2 precursor was heated in pure oxygen atmosphere at 3℃min -1 The temperature was raised to 500°C at a heating rate of 100°C and kept at that temperature for 300 minutes for pre-oxidation;

[0078] S4, high temperature solid phase lithium insertion: the precursor obtained after sintering was mixed evenly with LiOH·H2O with a lithium atom stoichiometric ratio of 1:1.60. Subsequently, the collected black precursor was placed in a muffle furnace and heated at 5℃min in an oxygen atmosphere. -1 The temperature was raised to 600°C and kept for 480 minutes. The temperature was then raised to 950°C and kept for 900 minutes for solid phase lithium insertion reaction. After calcination, the single crystal positive electrode material Li 1.2 Ni 0.21 Mn 0.59 O2;

[0079] S5, mixing the lithium-rich manganese-based single crystal positive electrode material and Al2O3 solid phase uniformly, and annealing at 400°C to obtain Al2O3-coated lithium-rich manganese-based single crystal positive electrode material Li 1.2 Ni 0.21 Mn 0.59 O2@Al2O3, the coating amount of Al2O3 is 4wt% of the lithium-rich manganese-based single crystal positive electrode material.

[0080] A positive electrode plate is prepared by coating a slurry made of Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material, a conductive agent, a binder and a solvent.

[0081] A lithium-ion battery, comprising the positive electrode sheet and the negative electrode sheet;

[0082] The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.

[0083] Comparative Example 1

[0084] (1) Solution preparation: Prepare a transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O. 2+ , Mn 2+ The molar ratio of Ni is 1:3. 2+ , Mn 2+ The sum of the concentrations is 2 mol / L. Prepare 4 mol / L ammonia water and 2 mol / L NaOH solution;

[0085] (2) Preparation of precursor: 2 L of transition metal salt solution was added to a reactor with a nitrogen atmosphere and a rotation speed of 800 rpm at a rate of 0.2 L / h. 4 mol / L of ammonia water was added to the reactor as a complexing agent. At the same time, 2 mol / L of NaOH solution was pumped into the reactor. The flow rate of the alkaline solution was adjusted to maintain the pH value between 11.3 and 11.4. A coprecipitation reaction was performed to prepare the precursor [Ni 0.25 Mn 0.75 ](OH)2. As the size of the hydroxide precursor increases, samples are taken every 2 hours. 50 When the particle size reaches 1-2 microns, the heating is turned off after the reaction is completed, and the precursor is washed with water and filtered after aging for 12 hours;

[0086] (3) Precursor pre-oxidation: The lithium-rich manganese precursor is placed in a pure oxygen atmosphere at 3°C ​​min -1 The temperature was raised to 500°C at a heating rate of 100°C and kept at that temperature for 300 minutes for pre-oxidation;

[0087] (4) High-temperature solid-phase lithium insertion: The above-obtained precursor was mixed evenly with LiOH·H2O with a lithium atom stoichiometric ratio of 1:1.55. Subsequently, the collected black precursor was placed in a muffle furnace and heated at 3°C ​​min in an oxygen atmosphere. -1 The temperature was raised to 550°C and kept for 300 min. The temperature was then raised to 870°C and kept for 720 min for solid phase lithium insertion reaction. After calcination, the single crystal positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2.

[0088] Comparative Example 2

[0089] The difference from Comparative Example 1 is:

[0090] (1) Solution preparation: Prepare a transition metal salt solution containing NiSO4·6H2O and MnSO4·H2O.2+ , Mn 2+ The molar ratio is 25:55;

[0091] (2) Preparation of lithium-rich manganese-based small-particle precursor: The preparation process is the same as in Example 1 to obtain a precursor with a composition of [Ni 0.3125 Mn 0.6875 ](OH)2-rich lithium-manganese-based precursor;

[0092] (3) High-temperature solid-phase lithium insertion: The amount of lithium source added and the calcination process were the same as in Example 1, except that the calcination temperature was raised to 850° C. and then kept at this temperature for 720 min to obtain a composition of approximately Li 1.2 Ni 0.25 Mn 0.55 Lithium-rich manganese-based single crystal positive electrode material for O2.

[0093] Comparative Example 3

[0094] The difference from Comparative Example 1 is that in the high-temperature solid-phase lithium insertion stage, the calcination temperature is changed to 850°C. Specifically: High-temperature solid-phase lithium insertion: The amount of lithium source added and the calcination process are the same as in Example 1, except that the calcination temperature is raised to 850°C and then kept warm for 720 minutes to obtain a composition of about Li 1.2 Ni 0.2 Mn 0.6 Lithium-rich manganese-based single crystal positive electrode material for O2.

[0095] Comparative Example 4

[0096] The difference from Comparative Example 1 is that in the high-temperature solid-phase lithium insertion stage, the calcination temperature is changed to 830°C. Specifically, the amount of lithium source added and the calcination process are the same as in Example 1, except that the calcination temperature is increased to 830°C and then kept warm for 720 minutes to obtain a composition of about Li 1.2 Ni 0.2 Mn 0.6 Lithium-rich manganese-based single crystal positive electrode material for O2.

[0097] Comparative Example 5

[0098] The difference from Comparative Example 1 is that in the high-temperature solid-phase lithium insertion stage, the calcination temperature is changed to 890°C and then kept warm for 720 minutes. Specifically:

[0099] High temperature solid phase lithium insertion: The amount of lithium source added and the calcination process are the same as in Example 1, except that the calcination temperature is raised to 890°C and then kept for 720 min to obtain a composition of about Li 1.2 Ni 0.2 Mn 0.6 Lithium-rich manganese-based single crystal positive electrode material for O2.

[0100] The electrochemical performance test results of the button cells assembled with the lithium-rich manganese-based single crystal positive electrode materials obtained in the above examples and comparative examples are shown in the following table:

[0101]

[0102] As can be seen from the table, the lithium-rich manganese-based single crystal positive electrode material coated with Al2O3 solid phase has little difference with the lithium-rich manganese-based single crystal positive electrode material in terms of discharge capacity and initial capacity, but the capacity retention rate after 100 cycles is significantly higher for the lithium-rich manganese-based single crystal positive electrode material coated with Al2O3 solid phase than for the lithium-rich manganese-based single crystal positive electrode material, proving that the lithium-rich manganese-based single crystal positive electrode material coated with Al2O3 solid phase has excellent performance.

[0103] Depend on Figure 1 It can be seen that the particle size of the primary particles of the precursor is in the range of 1-4um and is arranged in a discrete state, which is conducive to the lithiation reaction in the subsequent sintering process to form a small-particle single-crystalline positive electrode material.

[0104] Depend on Figure 2 It can be seen that the single crystal cathode material is distributed discretely as a whole, with an average particle size of about 1-4 μm. A lower particle size is beneficial to Li + Rapid disengagement.

[0105] Depend on Figure 3 It can be seen that the single crystal positive electrode material solid-phase coated with Al2O3 did not show obvious capacity decay during the long cycle process, and the capacity retention rate was more than 90% after 100 cycles at 1C, indicating that the presence of Al2O3 inhibited the side reaction between small-particle single crystals and the electrolyte, and slowed down the capacity decay.

[0106] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing an Al2O3 solid-phase coated lithium-rich manganese-based single crystal positive electrode material, characterized in that: The following steps are involved: S1. Solution preparation: prepare a transition metal salt solution at a molar ratio of Ni:Mn=1:(2.2-3), and simultaneously prepare a NaOH aqueous solution and an NH3·H2O aqueous solution; S2. Preparation of small particle size precursor: The transition metal salt solution, NaOH aqueous solution and NH3·H2O aqueous solution are slowly pumped into a reactor containing NaOH and deionized water at the same time, and the pH value of the reaction is controlled to be maintained at 11-12. After the reaction is completed, [Ni x Mn y ](OH)2 precursor, wherein 0.25≤x≤0.3125,0.6875≤y≤0.75, the [Ni x Mn y ]The particle size of the (OH)2 precursor is 1-4 microns; S3, small particle size precursor surface pre-oxidation: the [Ni x Mn y ](OH)2 precursor is pre-sintered in a pure oxygen atmosphere; S4, the pre-sintered [Ni x Mn y ](OH)2 precursor is mixed with lithium source and calcined twice in oxygen atmosphere to obtain submicron-sized lithium-rich manganese-based single crystal cathode material Li 1.2 Ni x Mn y O2, where 0.20≤x≤0.25, 0.55≤y≤0.60; S5, mixing the lithium-rich manganese-based single crystal positive electrode material and Al2O3 solid phase uniformly, and annealing at 400-500°C to obtain Al2O3-coated lithium-rich manganese-based single crystal positive electrode material Li 1.2 Ni x Mn y O2@Al2O3.

2. The method for preparing an Al2O3 solid phase coated lithium-rich manganese-based single crystal positive electrode material according to claim 1, characterized in that: In step S1, Ni 2+ and Mn 2+ The total concentration is 2-4 mol L -1 ; The concentration of the NaOH aqueous solution is 4-6 mol L -1 The concentration of the NH3·H2O aqueous solution is 2-6 mol L -1 .

3. The method for preparing an Al2O3 solid phase coated lithium-rich manganese-based single crystal positive electrode material according to claim 1, characterized in that: In step S1, the transition metal salt is selected from one of sulfate, chloride and nitrate, and the sulfate is NiSO4·6H2O and / or MnSO4·H2O.

4. The method for preparing an Al2O3 solid phase coated lithium-rich manganese-based single crystal positive electrode material according to claim 1, characterized in that: During the preparation of the small-particle precursor in step S2, the reaction temperature is controlled at 50-55° C., and stirring is performed continuously in an inert protective gas atmosphere at a stirring rate of 700-900 rpm.

5. The method for preparing an Al2O3 solid phase coated lithium-rich manganese-based single crystal positive electrode material according to claim 1, characterized in that: The pre-sintering temperature in step S3 is 400-500° C. and the time is 300-360 min.

6. The method for preparing an Al2O3 solid phase coated lithium-rich manganese-based single crystal positive electrode material according to claim 1, characterized in that: In step S4, the lithium source is selected from at least one of LiOH·H2O, LiNO3, and Li2CO3; the pre-sintered [Ni x Mn y ]The molar ratio of the (OH)2 precursor to the lithium source is 1:(1.50-1.60).

7. The method for preparing an Al2O3 solid phase coated lithium-rich manganese-based single crystal positive electrode material according to claim 1, characterized in that: The secondary calcination in step S4 is specifically as follows: heating to 500-600°C at a heating rate of 2°C / min-5°C / min in an oxygen atmosphere, and keeping the temperature for 6-8 hours for sintering; then heating to 800-950°C, and keeping the temperature for 10-15 hours for solid phase lithium insertion reaction.

8. The method for preparing an Al2O3 solid phase coated lithium-rich manganese-based single crystal positive electrode material according to claim 1, characterized in that: The coating amount of Al2O3 is 1-5wt% of the lithium-rich manganese-based single crystal positive electrode material.

9. A positive electrode plate, obtained by coating a slurry made of Al2O3 solid phase coated lithium-rich manganese-based single crystal positive electrode material prepared by the preparation method according to any one of claims 1 to 8, a conductive agent, a binder and a solvent.

10. A lithium ion battery comprising the positive electrode sheet and the negative electrode sheet according to claim 9; The active material on the negative electrode plate is selected from one or more of graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode and lithium-carbon negative electrode material.

Citation Information

Patent Citations

  • Preparation method of anode material of Al2O3-cladding manganese-based laminated lithium battery

    CN101777643A

  • Method for preparing lithium-enriched manganese-based anode material of nano-oxide-coated lithium ion battery

    CN103441252A

  • Synthesis method for high-performance lithium-rich manganese-based positive electrode material

    CN106654249A

  • Single crystal lithium-rich manganese-based anode material, preparation method thereof, lithium ion battery

    CN108598457A

  • Positive electrode material sintering device and sintering method

    CN110864545A